After Newtown : Guns in America / [videorecording (DVD)] - Harris, Richard (Producer); Harris, Richard (Producer); Silvers, Jonathan; Silvers, Jonathan (Public Broadcasting Service, 2013)
An unprecedented exploration of America's enduring relationship with firearms. From the first European settlements in the New World to frontier justice; from 19th Century immigrant riots to gangland violence in the Roaring Twenties; from the Civil War to Civil Rights, guns have been at center of our national narrative for four hundred years. Americans have relied on guns to sustain communities, challenge authority, and keep the peace. Efforts to curtail their distribution and ownership have triggered epic political battles. On one side, the cry for gun control gets louder with each mass shooting.